2022
DOI: 10.3174/ajnr.a7500
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Noncontrast Head CT Reports for Common Findings Using Natural Language Processing

Abstract: BACKGROUND AND PURPOSE: Prioritizing reading of noncontrast head CT examinations through an automated triage system may improve time to care for patients with acute neuroradiologic findings. We present a natural language-processing approach for labeling findings in noncontrast head CT reports, which permits creation of a large, labeled dataset of head CT images for development of emergent-finding detection and reading-prioritization algorithms. MATERIALS AND METHODS:In this retrospective study, 1002 clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The annotation rules for each label were clearly defined, referring to the annotation rules from the cited study [22]. Furthermore, incorporating insights from Lorga's study, labels frequently identified in noncontrast head CT scans, such as hemorrhage, fracture, and pneumocephalus, were also included [23].…”
Section: ) Experimentsmentioning
confidence: 99%
“…The annotation rules for each label were clearly defined, referring to the annotation rules from the cited study [22]. Furthermore, incorporating insights from Lorga's study, labels frequently identified in noncontrast head CT scans, such as hemorrhage, fracture, and pneumocephalus, were also included [23].…”
Section: ) Experimentsmentioning
confidence: 99%